The Effect of Corporate Social Responsibility (CSR) Disclosure and Firm Size on Earnings Management - Nggebu, Carolline Mathilda; Rahman, Aulia Fuad (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
A company’s profit is usually presented on an accrual basis. However, this accrual basis provides flexibility for management to choose the accounting methods used. There are many examples of earnings management practices in Indonesia. Corporate social responsibility (CSR) can be one way to overcome earnings management even whem firm size partialy has a positive impact on earnings management. The study aims to quantitatively analyze the impact of corporate social responsibility disclosure and company size on the revenue management of Indonesian Stock Exchange-listed banking companies from 2019 to 2021. This study uses literature research and documents to collect secondary data from annual corporate reports published on the official website of the Indonesia Stock Exchange. This population consists of 47 emitters, from which he selects 29 samples of his emitters using targeted sampling methods according to characteristics determined by researchers. Descriptive statistical analysis and regression results for panel data indicate that corporate social responsibility is not a determinant of revenue management, but firm size.